Dampak Era Digital terhadap Penggunaan Bahasa Jawa Halus di Kalangan Anak-anak Desa Sribasuki Batanghari Lampung Timur - Arivani, Vika (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2024)
This research aims to understand how the younger generation learns and uses subtle Javanese, and the influence of technology on this process. The research was conducted in Sribasuki Village, Batanghari, East Lampung, using qualitative methods with in-depth interviews. The findings show that coarse Javanese (ngoko) is more commonly used in children's daily conversations, while their proficiency in fine Javanese is declining. Technology and social media play a role in accelerating this change, encouraging children to prefer Indonesian or ngoko which is considered more modern. The research also highlights the importance of parents' role in supporting the learning of subtle Javanese by utilizing technology. The results of this study provide guidance for educators and parents in preserving Javanese language and culture amidst the influence of globalization.